Music Director Strategies within the Worship Music Team: A Study at BFA Church Yogyakarta - Siska Friscilia; Tanesya Hotris Samosir (Institut Agama Kristen Negeri Manado, 2024)
Music is an essential element of worship services, entrusted to music directors for arrangement and leadership. This study examines the strategies employed by music directors at BFA Church Yogyakarta. Utilizing qualitative methods, data were collected through purposive sampling of two music directors, with observations, interviews, and document analysis serving as primary data sources. Data were analyzed using the Miles and Huberman model, involving data reduction, display, and conclusion drawing. Findings emphasize the critical role of the music director in managing the worship music team, highlighting the importance of strategic planning and leadership in delivering effective worship services. Guided by Mark Cole’s theoretical framework, the identified strategies are organized into pre-rehearsal, mid-week rehearsal, and Sunday worship stages, closely aligned with BFA Church practices. Implementing structured strategies across these stages promotes team coordination and enhances the quality of worship music, contributing to a meaningful worship experience for the congregation.